Use of a serious game simulation to build early childhood staff capacity for reducing unintentional childhood injuries. (September 2022) - Hanna, Jennifer L.; Wright, Michelle F.; Azar, Sandra T.
Highlights: Proof-of-concept study testing feasibility of one phase of Home Safety Hero ( HSH ). Small sample of EC home visitors found HSH to be engaging and promote knowledge. Game format offers potential for meeting the needs of early childhood professionals. Abstract: Introduction: Unintentional home injuries are common and costly, with over 1.6 million occurring among U.S. children ages 0–4 in 2018. Home visitors and other early childhood professionals can provide valuable prevention education and intervention to reduce unintentional injury risk for children. This proof-of-concept study aimed to test the feasibility of the first phase of Home Safety Hero, a software-based serious game simulation that trains users in identification of home safety risks, as a capacity building tool for early childhood professionals. Methods: The game simulation's potential for knowledge promotion and engagement in a sample of home visitors was explored based on play of the first phase. Repeated measures ANOVAs were used to assess learning via reaction time, and engagement was measured via the User Engagement Scale (UES). Results: Reaction time (i.e., average time to identify hazards) improved from the first to last levels in both single and mixed category levels in this trial. Participant indicated agreement with four subscales of engagement measured by the UES, and neutral to agree on a fifth subscale, focused attention. Conclusions: We propose that this game simulation can meet the unique training needs of early childhood professionals while promoting home safety knowledge that can improve prevention work with families. Participant feedback was largely positive, and results suggest that the game simulation is engaging and contributes to knowledge. Practical Applications: The Home Safety Hero serious game simulation is a flexible training option that appeared to be feasible for reducing time to hazard identification among home visitors in this proof-of-concept study. The design of the game simulation has utility in meeting the specialized training needs of early childhood professionals and potential to build their capacity to provide direct intervention around home safety, reducing risk for unintentional injury among children.